Three new species of Gladiolus (Iridaceae) from South Africa, a major range extension for G. rubellus and taxonomic notes for the genus in southern and tropical Africa - J. C. Manning (Bothalia: African Biodiversity & Conservation, 2009)
Three new species of Gladiolus L. are described from South Africa.  G. dolichosiphon is the second known member of series Blandus from the mountains of the Little Karoo in Western Cape, and is distinguished from other members of the long tubed, pink-flowered G. carneus complex by its 5 or 6 linear leaves, creamy pink to salmon flowers with a tube 30-50 mm long and longer than the dorsal tepal, and its late summer flowering. G. karooicus from the Klein Roggeveld and the northern foothills of the Witteberg, is a spring-flowering species allied to G. permeabilis but has bright, canary-yellow flowers with the lower part of the lower tepals involute and conspicuously auriculate.  G. reginae is an edaphic endemic of the Sekhuk- huneland Centre of Floristic Endemism in Mpumalanga, and flowers in autumn. It is evidently a glabrous member of section Densiflorus series Scabridus, distinguished by its long-tubed flowers, streaked with red on the lower tepals and blotched with red in the throat. Anomalously, however, it has the tubular inner bracts and large capsules diagnostic of section Ophiolyza series Oppositiflorus. A re-examination of the morphology suggests that series Scabridus is better placed in section Ophiolyza and a slightly revised classification of Gladiolus in southern Africa is proposed. We also propose the replacement name G. sulculatus for the Tanzanian species, G. sulcatus Goldblatt, a later homonym of G. sulcatus Lam. Finally, a recent sighting of what appears to be G. rubellus from northern Namibia constitutes the first record of this species in the country and a major range extension from its previous known occurrence in southeastern Botswana.